Automated Total IntraVenous Anesthesia (amTIVA) from induction to recovery - Luis A Paz (2014)
This paper presents a multi-functional automatic control approach for total intravenous anesthesia (TIVA) administration, valid for several drug combinations and able to run autonomously during the three main phases of general anesthesia: induction, maintenance and recovery. While using this standalone TIVA module, named as amTIVA, the anesthesiologist has the crucial role of system supervisor. Bolus administration, open-loop target controlled infusion (TCI) and closed-loop controlled infusion modes are implemented and available for the control of the two main components of anesthesia: the neuromuscular blockade and the depth of anesthesia. This multi-functional module is implemented in the GALENO Platform and was successfully tested in more than thirty clinical cases.